2010
DOI: 10.1103/physrevb.82.085417
|View full text |Cite
|
Sign up to set email alerts
|

Quasiperiodic Pb monolayer on the fivefoldi-Al-Pd-Mnsurface: Structure and electronic properties

Abstract: Lead is one of few elements that adopts a pseudomorphic structure when deposited on quasicrystalline substrates. We present a structural model of quasiperiodic Pb overlayers formed on the fivefold surface of an icosahedral Al-Pd-Mn quasicrystal at two different coverages close to saturation. The skeleton of the Pb monolayer is formed by a network of "starfish" ͑SF͒ clusters formed at the initial stages of Pb deposition, as studied in detail in our previous work ͓Ledieu et al., Phys. Rev. B 79, 165430 ͑2009͔͒. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To further support this conclusion, the electronic properties have been calculated for both periodic and aperiodic unsupported Pb monolayers (triangular and square lattices). It follows that the periodic structures exhibit also a deep pseudo‐gap at E F , while only a shallow minimum is obtained for the unsupported quasiperiodic Pb monolayer 17…”
Section: Adsorption Sites and Pseudomorphic Monolayersmentioning
confidence: 93%
See 2 more Smart Citations
“…To further support this conclusion, the electronic properties have been calculated for both periodic and aperiodic unsupported Pb monolayers (triangular and square lattices). It follows that the periodic structures exhibit also a deep pseudo‐gap at E F , while only a shallow minimum is obtained for the unsupported quasiperiodic Pb monolayer 17…”
Section: Adsorption Sites and Pseudomorphic Monolayersmentioning
confidence: 93%
“…The reduction in the electronic density of states (pseudo‐gap) at the Fermi level (E F ) measured on the clean Al‐Pd‐Mn quasicrystal surface is preserved and even larger on this Pb monolayer. First attributed to the quasiperiodic ordering of the structure, the ab initio calculations have demonstrated that the hybridization of the Pb p states with the substrate was responsible for the presence of this pseudo‐gap 17. To further support this conclusion, the electronic properties have been calculated for both periodic and aperiodic unsupported Pb monolayers (triangular and square lattices).…”
Section: Adsorption Sites and Pseudomorphic Monolayersmentioning
confidence: 93%
See 1 more Smart Citation
“…The sticking coefficient of an adatom on a surface vanishes to zero if the binding energy of the adatom to the surface is negligible or if there is inefficient dissipation of kinetic energy of the adatom to the surface through phonon excitation. 47 It was speculated that the latter case is responsible for the vanishing sticking coefficient of Pb atoms on the Al-based quasicrystals. The Pb layer on the Al-based quasicrystals was highly dense (0.09 atoms/Å 2 ), 47 compared to the Pb layer on i-Ag-In-Yb (0.004-0.007 atoms/Å 2 ), 26 one order of magnitude less).…”
Section: Magic Heights Of Crystalline Pb Islandsmentioning
confidence: 99%
“…47 It was speculated that the latter case is responsible for the vanishing sticking coefficient of Pb atoms on the Al-based quasicrystals. The Pb layer on the Al-based quasicrystals was highly dense (0.09 atoms/Å 2 ), 47 compared to the Pb layer on i-Ag-In-Yb (0.004-0.007 atoms/Å 2 ), 26 one order of magnitude less). The sparse layer on i-Ag-In-Yb should be less rigid, and therefore should exhibit a broader phonon spectrum and be more efficient at absorbing kinetic energy.…”
Section: Magic Heights Of Crystalline Pb Islandsmentioning
confidence: 99%